EFEKTIVITAS IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK ZEM SILVER DEMAK - Eko Sasono; Nila Citra Prabastari (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract This study aims to determine the effect of attention on purchasing decisions for Zem Silver Demak products. The population in this research is Zem Silver Demak consumers. The sample of this research is 90 respondents. The data analysis technique used multiple regression analysis, hypothesis testing, simultaneous F-test and coefficient of determination. The results show that Attention, interest, desire and action have a positive and significant effect on purchasing decisions for Zem Silver Demak products